2020
DOI: 10.1088/1755-1315/448/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

The trade-off between Poverty and Environmental Degradation: Evidence from Indonesia

Abstract: Poverty and environmental issues are correlated. Many reports suggest that poverty contributes to environmental degradation. Therefore, it is believed that the improvement of the quality of the environment must be started by alleviating poverty. The objectives of this study are to find the impact of poverty to environmental degradation and vice versa. This study uses data panel from 33 provinces in Indonesia from 2012 to 2017. Contrary to the belief, the result shows that the effort to reduce poverty resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
3
5
0
2
Order By: Relevance
“…Strict government regulations related to environmental protection will actually lead to an increase in the number of poor people due to limited access to natural resources. The research results of Setyadharma et al, (2020) are in line with research by AK. Duraiappah, (1998) which concluded that initially the poor were not the direct cause of environmental damage.…”
Section: Literature Reviewsupporting
confidence: 87%
See 3 more Smart Citations
“…Strict government regulations related to environmental protection will actually lead to an increase in the number of poor people due to limited access to natural resources. The research results of Setyadharma et al, (2020) are in line with research by AK. Duraiappah, (1998) which concluded that initially the poor were not the direct cause of environmental damage.…”
Section: Literature Reviewsupporting
confidence: 87%
“…The results of this study support research by (Setyadharma et al, 2020). Provincial data in Indonesia shows that areas that have high economic growth are not followed by a decrease in poverty rates (Oktavilia et al, 2018).…”
Section: Positive Effects Of Poverty On the Environmental Quality Indexsupporting
confidence: 86%
See 2 more Smart Citations
“…They arguments implied that policy to reduce income inequality should not lead to an increase in carbon emissions, except in the case of low-income countries, a trade-off is absent. In the case of Indonesia, Setyadharma et al. (2020) , said that efforts to reduce poverty have an impact on decreasing environmental quality.…”
Section: Introductionmentioning
confidence: 99%